All‐trans‐retinoid acid induces the differentiation of P19 cells into neurons involved in the PI3K/Akt/GSK3β signaling pathway. Issue 11 (21st January 2020) - Fu, Fang; Li, Lu‐Shan; Li, Ru; Deng, Qiong; Yu, Qiu‐Xia; Yang, Xin; Pan, Min; Han, Jin; Zhen, Li; Zhang, Li‐Na; Lei, Ting‐Ying; Li, Dong‐Zhi; et al.
Abstract: The pluripotent mouse embryonal carcinoma cell line P19 is widely used as a model for research on all‐trans‐retinoid acid (RA)‐induced neuronal differentiation; however, the signaling pathways involved in this process remain unclear. This study aimed to reveal the molecular mechanism underlying the RA‐induced neuronal differentiation of P19 cells. Real‐time quantitative polymerase chain reaction and Western blot analysis were used to determine the expression of neuronal‐specific markers, whereas flow cytometry was used to analyze cell cycle and cell apoptosis. The expression profiles of messenger RNAs (mRNAs) in RA‐induced neuronal differentiation of P19 cells were analyzed using high‐throughput sequencing, and the functions of differentially expressed mRNAs (DEMs) were determined by bioinformatics analysis. RA induced an increase in both class III β‐tubulin (TUBB3) and neurofilament medium (NEFM) mRNA expression, indicating that RA successfully induces neuronal differentiation of P19 cells. Cell apoptosis was not affected; however, cell proliferation decreased. We found 4117 DEMs, which were enriched in the phosphoinositide 3‐kinase/protein kinase B (PI3K/Akt) signaling pathway, Wnt signaling pathway, and cell cycle. Particularly, a few DEMs could be identified in the PI3K/Akt signaling pathway networks, such as PI3K, Akt, glycogen synthase kinase‐3β (GSK3β), cyclin‐dependent kinase 4 (CDK4), P21, and Bax. RA significantly increased the protein expression of PI3K, Akt, phosphorylated Akt, GSK3β, phosphorylated GSK3β, CDK4, and P21, but it reduced Bax protein expression. The Akt inhibitor affected the increase of TUBB3 and NEFM mRNA expression in RA‐induced P19 cells. The molecular mechanism underlying the RA‐induced neuronal differentiation of P19 cells is potentially involved in the PI3K/Akt/GSK3β signaling pathway. The decreased cell proliferation ability of neuronally differentiated P19 cells could be associated with the expression of cell cycle proteins. Abstract : This study aimed to reveal the molecular mechanism underlying all‐trans‐retinoid acid (RA)‐induced neuronal differentiation of P19 cells. The molecular mechanism underlying the RA‐induced neuronal differentiation of P19 cells is potentially involved in the PI3K/Akt/GSK3β signaling pathway. The decreased cell proliferation ability of neuronally differentiated P19 cells could be associated with the expression of cell cycle proteins.